USING CURRENT INFORMATION TECHNOLOGY IN EDUCATION - Maqsudov Ravshan Khasanovich (Journals Park Publishing, 2022)
All domains receive the same attention in our nation today. especially in the area of education. As a result, teaching plays a crucial role in the development of young professionals as a programmatic direction. In particular, it is now a top concern to employ contemporary technology to educate children and to integrate them into the educational system. The author of this article thoroughly explains the function of pedagogical technology and contemporary technologies in pedagogy.
Keywords: teaching methods, contemporary technologies, curriculum, students, staff development, etc.